Kuka pelkää globalisaatiota? Suomalaisten pelot ja toiveet sekä toteutuneet vaikutukset - Annu Kotiranta (The Research Institute of the Finnish Economy (ETLA), 2008)
According to EVA's annual attitude and value survey, two out of three Finns believe that globalization means loosing increasing amounts of jobs to low-cost-countries. However, 70 percent of the respondents think that their job is not easily transferrable and only 8 % are afraid that their own job is going to be offshored. As both national and international research indicates that the employment effects of globalization are rather modest, who is afraid of globalization and why? In this analysis it is found that highly educated, service sector, and male employees are the least afraid of globalization. Additionally, it is noticed that attitudes are more important than actual labour market experiences, when it comes to the expectations and perceptions of globalization.
Keywords: F02; Z10; 330; Globalization; internationalization; attitudes; prejudice; Globalisierung; Beschäftigungseffekt; Qualifikation; Meinung; Finnland